Empowerment of the Creative Economy during the Pandemic in the Kuta Mandalika - Eka Agustiani; ranip fahmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2022)
This study aims to analyze forms of creative economic empowerment and analyze business sustainability during the pandemic in the Mandalika Special Economic Zone, Kuta Village, Pujut District, Central Lombok Regency. The approach used is a qualitative descriptive method. Data collection techniques in this study used the methods of observation, interviews and documentation. The technique of checking the validity of the data used is the triangulation technique. The data analysis method used is data reduction, data presentation and drawing conclusions. The results of this study found that forms of community economic empowerment through a sustainable creative economy include Entrepreneurship Training for Making Seaweed Dodol, Crackers and Sticks, Training for Makeup and Hair and Training and Distribution of Screen Printing Tools. Meanwhile, training in the cultivation and processing of Oyster Mushrooms is not sustainable. Empowerment activities have an impact on increasing the skills of participants so that they are given business capital in the form of equipment and equipment so that they obtain business income.